Analysis of the Application of Material Requirement Planning Method in Nature to Achieve the Production Targets of the Moraja Donggala Social Forestry Business Group - Farid; Sri Haryani; Fenny Aldini (International Journal of Health, Economics, and Social Sciences (IJHESS), 2022)
This study aims to analyze the Application of Material Requirement Planning (MRP) in achieving production targets in the Moraja Social Forestry Business Group (KUPS). The type of research used is a descriptive qualitative method using Material Requirement Planning (MRP) analysis. The results showed that KUPS Moraja has not been able to fully implement MRP, which is in the form of a Master Production Schedule and is on a manufacturing or manufacturing scale. Then related to planning, scheduling orders and controlling raw material inventory items have been carried out even with a conventional system where the Master Production Schedule (MPS) KUPS Moraja carries out or schedules production once a month in week 2 (two) or if there are orders from customers so that in a year the production order schedule occurs 12 (twelve) times. Kups Moraja on Bill of Material (BOM) consists of three processes, namely the drying, grinding, and packing processes. Furthermore, the Inventory Record (Inventory Record), it can be known that the raw materials used during the 2021 period were 39 kg 06 ounces of Moringa leaves. Then for the lead time, the entire production process takes 7 (seven) days, which consists of stages, namely the drying process of Moringa tea takes 5 days, while the grinding process of Moringa tea takes 1 day and the packaging process takes 1 day. Overall, the supply of Moringa raw materials has been controlled using conventional techniques.